2017
DOI: 10.1016/j.chemosphere.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of low-molecular-weight organic acids on mobilization of arsenic and lead from multi-contaminated soils

Abstract: A batch experiment was conducted to examine the combined effects of three common low-molecular-weight organic acids (LMWOAs) on the mobilization of arsenic and lead in different types of multi-contaminated soils. The capacity of individual LMWOAs (at a same molar concentration) to mobilize soil-borne As and Pb varied significantly. The combination of the organic acids did not make a marked "additive" effect on the mobilization of the investigated three elements. An "antagonistic" effect on element mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 53 publications
2
21
2
Order By: Relevance
“…The results of arsenic extraction in the washing experiment indicated that biodegradable acids, such as oxalic, citric and its combination with ascorbic, can be considered as a means of remediating As-contaminated soils. This is consistent with the outcome of other authors [ 31 , 47 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of arsenic extraction in the washing experiment indicated that biodegradable acids, such as oxalic, citric and its combination with ascorbic, can be considered as a means of remediating As-contaminated soils. This is consistent with the outcome of other authors [ 31 , 47 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…During the past decades, several studies have been conducted to evaluate the effectiveness of various single chemical agents on arsenic removal in soils and sediments, such as HCl acid, H 3 PO 4 acid, ethylenediaminetetraacetic acid (EDTA), Na 2 EDTA, and surfactants [ 25 , 26 , 27 , 28 ]. Some biodegradable organic acids (e.g., oxalic acid, citric acid, and ascorbic acid), which are active components in the root exudates of plants [ 29 , 30 ], were also reported to have a significant effect on arsenic extraction from soils and sediments [ 31 , 32 , 33 ]. These acids attain much higher anionic metal extractions compared to other chelate agents, such as EDTA or Na 2 EDTA [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). This was accompanied by the release of trace elements (As, Ba, Cd, Co, Cr, Cu, Ni, Pb, Sr and Zn) that were likely to be bound to these oxides, as shown in previous work (Onireti and Lin, 2016;Onireti et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…This is not in agreement with many other findings that show Pb is favourably bound to oxides of iron and manganese [32][33][34][35][36]. Previous investigation suggested that Pb in contaminated soils at this site was mainly in the form of lead sulfate [37]. Consequently, the mobilization of Pb was not related to the dissolution of Fe, Mn, and Al oxides.…”
Section: Discussioncontrasting
confidence: 91%